Clinical manifestations of beta thalassemia major in the pediatric population: A systematic review (Research, Society and Development, 2023)
This study aimed to investigate information in the literature regarding the clinical manifestations associated with beta thalassemia major (BTM) in pediatric patients. To this end, a systematic review of the literature was carried out following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The descriptors “beta thalassemia”, “signs and symptoms” and “child” were used on the search platforms PubMed, Scielo, Science Direct, Science.gov and LILACS, to search for articles published between 2013 and 2023. After evaluating the databases data, 12 articles were selected to compose this work. All articles were published in English and the majority of them (n=7) had Egypt as their country of origin. Regarding the nature of the studies, it was observed that the majority of them were cross-sectional (n=7), followed by case-control studies (n=4) and only one of the cohort type. The articles described the identification of clinical manifestations in pediatric patients with BTM and the importance of their identification. It has been reported that dyslipidemias (changes in HDL-cholesterol, LDL-cholesterol and triglycerides) are related to cardiovascular changes in patients with BTM. Increased vascular endothelial growth factor was associated with the development of pulmonary hypertension. Excessive iron deposition has been associated with ventricular dysfunction, atherosclerosis, kidney and pancreatic disorders. Osteopenia associated with parathyroid hormonal changes have also been reported in BTM. Thus, it is concluded that BTM is the most common autosomal hereditary blood disease in the population and that its clinical manifestations have a negative impact on the health-related quality of life of pediatric patients.